cos cos sin sin tan tan

(a+b) = cosacosb-sinasinb (a-b)= cosacosb+sinasinb (a+b)= sinacosb+ cosasinb (a-b)= sinacosb - cosasinb (a+b) = tan a + tan b / 1 - tanatanb (a-b) = tan a - tan b / 1 + tanatanb

sin 2a = 2 sinacos a cos 2a = cos^2 a - sin^2 a = 1 - 2sin^2 a = 2cos^2 a - 1 tan 2a = sin 2a/cos2a = 2 tan a / 1 -tan^2 a sin 1/2 a = +- akar (1 - cos a / 2) cos 1/2 a = +- akar ( 1 + cos a / 2) tan 1/2 a = sin 1/2 a / cos 1/2 a = +- akar (1-cos a / 1 + cos a) sin cos cos sin sin sin cos cos a a a a a a a a cos sin cos sin + + b b b b = = = = b b b b 1/2 1/2 1/2 1/2 = = = = [sin [sin [cos [cos (a+b) (a+b) (a+b) (a-b) + + sin sin cos cos (a-b)] (a-b)] (a-b)] (a+b)] = -1/2 [cos (a+b) - cos (a-b)

sin sin cos cos

2 [sin 1/2 (a+b).cos 1/2 (a-b)] 2 [cos 1/2 (a+b)sin 1/2 (a-b)] 2 [cos 1/2 (a+b)cos 1/2 (a-b)] -2 [sin 1/2(a+b) sin 1/2 (a-b)]

Sign up to vote on this title
UsefulNot useful